Bisphenols - Erkekoğlu, Pınar (IntechOpen, 2022)
Bisphenols are a group of abundant environmental chemicals. Many bisphenol derivatives, including bisphenol A (BPA), are used to manufacture plastics, epoxy resins, and other products. Thus, human exposure to bisphenols is inevitable. BPA may cause reproductive, developmental, and systemic toxic effects and there are questions about its potential impact, particularly on children's health and the environment. Due to these concerns, new alternatives are now being used; however, these alternatives also have a bisphenol chemical structure and may lead to toxicity in humans. This book focuses on the toxicity mechanisms, pathological conditions, detection methods, and regulations of bisphenol derivatives. It presents the latest findings on the toxic effects of BPA, diseases that may be related to bisphenol exposure, and the regulations of the US Food and Drug Administration, European Food Safety Authority, and European Union.